Renewable Energy Production from Energy Crops and Agricultural Residues (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Energies is open to submissions for a Special Issue on “Renewable Energy Production from Energy Crops and Agricultural Residues”. Biomass represents an important source of renewable and sustainable energy production. Its increasing consumption is mainly related to the increase in global energy demand and fossil fuel prices, but also to a lower environmental impact compared to non-renewable fuels. These factors take RED II directives into consideration. In the past, forestry interventions were the main supply source of biomass, but in recent decades two others sources have entered the international scene. These are dedicated energy crops and agricultural residues, which are important sources of biomass for biofuel and bioenergy. Below, we consider four main value chains: • Oil crops: Oil production from non-food oilseed crops (such as camelina, Crambe, safflower, castor, cuphea, cardoon, etc.), oil extraction, and oil utilization for fuel production. • Lignocellulosic crops: Biomass production from perennial grasses (miscanthus, giant reed, switchgrass, reed canary grass, etc.), woody crops (willow, poplar, Robinia, eucalyptus, etc.), and agricultural residues (pruning, maize cob, maize stalks, wheat chaff, sugar cane straw, etc.), considering two main transformation systems: 1. Electricity/heat production 2. Second-generation ethanol production • Carbohydrate crops (cereals, sweet sorghum, sugar beets, sugar cane, etc.) for ethanol production. • Fermentable crops (maize, barley, triticale, Sudan grass, sorghum, etc.) and agricultural residues (chaff, maize stalks and cob, fruit and vegetable waste, etc.) for production of biogas and/or biomethane.